Electrode catalyst and manufacturing method thereof

The electrode catalyst with a porous carrier and controlled carbon filling addresses performance deterioration in low humidity by preventing ionomer intrusion, maintaining stability across humidity variations.

JP2024178063APending Publication Date: 2024-12-24KK TOYOTA CHUO KENKYUSHO +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023096576
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing electrode catalysts experience performance deterioration in low humidity environments due to ionomer intrusion into the pores of porous carriers, leading to catalyst poisoning.

Method used

The electrode catalyst is designed with a porous carrier having a pore diameter of 6 nm to 20 nm, filled with carbon to a specific relative carbon loading, supporting catalyst particles within the pores to prevent ionomer intrusion and maintain performance across varying humidity levels.

Benefits of technology

The catalyst maintains high performance in both low and high humidity environments by suppressing ionomer penetration, ensuring stable catalytic activity and reduced proton transfer resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178063000001_ABST
    Figure 2024178063000001_ABST
Patent Text Reader

Abstract

To provide an electrode catalyst that exhibits less performance degradation in a low humidity environment and a manufacturing method thereof.SOLUTION: An electrode catalyst includes: a porous support having a pore size of more than 6 nm and 20 nm or less; catalyst particles supported within the pores of the porous support; and carbon filled within the pores. The electrode catalyst has a relative carbon loading of more than 0 g / mL and less than 0.23 g / mL. The electrode catalyst can be obtained by supporting catalyst particles within the pores of the porous support having a pore size of more than 6 nm and 20 nm or less, filling the pores with a carbon source, and immobilizing and carbonizing the carbon source.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode catalyst and a method for producing the same, and more particularly to an electrode catalyst which exhibits little performance degradation in a low humidity environment and a method for producing the same. [Background technology]

[0002] A polymer electrolyte fuel cell comprises a membrane electrode assembly (MEA) in which electrodes (catalyst layers) containing a catalyst are bonded to both sides of an electrolyte membrane. A gas diffusion layer is usually arranged on the outside of the catalyst layer. Furthermore, a current collector (separator) with a gas flow path is arranged on the outside of the gas diffusion layer. A polymer electrolyte fuel cell usually comprises a structure (fuel cell stack) in which a plurality of unit cells each consisting of such an MEA, gas diffusion layer, and current collector are stacked.

[0003] In a polymer electrolyte fuel cell, the catalyst layer is made of a composite of an electrode catalyst and a catalyst layer ionomer. The catalyst layer ionomer is a component necessary for supplying protons to the electrode catalyst. However, the catalyst layer ionomer is easily adsorbed onto the surface of the catalyst particles. When the acid groups of the catalyst layer ionomer are adsorbed onto the surface of the catalyst particles, this causes a decrease in catalytic activity. Such adsorption of the acid groups of the catalyst layer ionomer onto the surface of the catalyst particles and the resulting decrease in catalytic activity are more likely to occur in a low humidity environment than in a high humidity environment.

[0004] In order to solve this problem, various proposals have been made. For example, Patent Document 1 describes a porous porous material having a diameter of 100 nm to 300 nm, a pore size of 3 nm to 6 nm, and a specific surface area of ​​800 m 2 / g or more. The document describes that when a catalyst layer is prepared using monodispersed spherical carbon porous bodies, performance degradation due to catalyst poisoning can be suppressed by optimizing the diameter, pore size, and specific surface area of ​​the monodispersed spherical carbon porous bodies.

[0005] Patent Document 2 discloses an electrode catalyst that includes catalyst particles and a nitrogen-containing carbon membrane that covers the surfaces of the catalyst particles, the nitrogen-containing carbon membrane including micropores. The document describes that such an electrode catalyst has improved initial activity and durability compared to an electrode catalyst in which the surface of the catalyst particles is covered with a carbon film derived from polydopamine.

[0006] Patent Document 3 describes a catalyst for a catalytic converter comprising catalyst particles and a carbon film that covers the surface of the catalyst particles, the content of chloride ions per unit surface area of ​​the catalyst particles being 12.5 μg / m 2 An electrocatalyst is disclosed that is less than The document describes that when an electrode catalyst in which the surface of the catalyst particles is covered with a carbon film derived from an organic substance is washed, the chloride ions adsorbed on the surface of the catalyst particles are removed, thereby improving the initial activity compared to an electrode catalyst that is not washed.

[0007] As described in Patent Document 1, by supporting catalyst particles in the pores of a carbon porous body, it is possible to suppress performance degradation due to catalyst poisoning to a certain extent. However, if the pore diameter of the carbon porous body is excessively large, performance degradation due to catalyst poisoning may occur. This is thought to be because the larger the pore diameter, the easier it is for the ionomer to penetrate into the pores.

[0008] On the other hand, Patent Documents 2 and 3 describe that when catalyst particles are supported on the outer surface of a solid support, the performance of the electrode catalyst is improved by covering the surface of the catalyst particles with a nitrogen-containing carbon film or a carbon film. However, there has been no prior art proposal for a method capable of suppressing performance degradation in a low humidity environment for an electrode catalyst in which catalyst particles are supported on the surface of a porous support having a relatively large pore size. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent No. 7116564 [Patent Document 2] JP 2022-142887 A [Patent Document 3] JP 2020-136109 A Summary of the Invention [Problem to be solved by the invention]

[0010] An object of the present invention is to provide an electrode catalyst that exhibits little deterioration in performance in a low humidity environment, and a method for producing the same. [Means for solving the problem]

[0011] In order to solve the above problems, the electrode catalyst according to the present invention comprises: A porous carrier having a pore size of more than 6 nm and not more than 20 nm; Catalyst particles supported in the pores of the porous support; Carbon filled in the pores; Equipped with The relative carbon loading W represented by the formula (1) described below is greater than 0 g / mL and less than 0.23 g / mL.

[0012] The method for producing an electrode catalyst according to the present invention includes the steps of: A first step of preparing a catalyst precursor A in which catalyst particles are supported in pores of a porous support having a pore diameter of more than 6 nm and not more than 20 nm; a second step of preparing a liquid carbon precursor containing a carbon source, dropping the liquid carbon precursor into the catalyst precursor A in an amount 1.5 times or less of the pore volume of the catalyst precursor A to obtain a catalyst precursor B in which the liquid carbon precursor is filled in the pores; a third step of heat-treating the catalyst precursor B to obtain a catalyst precursor C in which the carbon source is fixed in the pores; a fourth step of heat-treating the catalyst precursor C in a non-oxidizing atmosphere at a temperature of 500° C. or more and 1000° C. or less to carbonize the carbon source; It is equipped with: Effect of the Invention

[0013] When a catalyst layer is made using an electrode catalyst in which catalyst particles are supported on a porous support with a pore size of more than 6 nm, the performance tends to decrease in a low humidity environment. This is thought to be because the ionomer penetrates into the pores and poisons the catalyst particles inside the pores. In contrast, when catalyst particles are loaded into the pores of a porous support with a pore size of more than 6 nm and then the pores are filled with carbon, the performance degradation in a low humidity environment is suppressed. This is thought to be because the carbon filled in the pores suppresses the penetration of the ionomer into the pores. [Brief description of the drawings]

[0014] [Figure 1] 1 shows the relative carbon loading of the electrode catalysts obtained in Examples 1 and 2 and Comparative Example 2. [Diagram 2] The mass activities of the electrode catalysts obtained in Examples 1 and 2 and Comparative Examples 1 and 2 are measured at a temperature of 82° C., a humidity of 30% RH, and an IR-corrected voltage of 0.84 V. [Diagram 3] 1 shows the mass activity of the electrode catalysts obtained in Examples 1 and 2 and Comparative Examples 1 and 2 at a temperature of 60° C., a humidity of 80% RH and an IR-corrected voltage of 0.84 V.

[0015] [Figure 4] FIG. 1 shows the relationship between relative carbon loading and mass activity at 82° C. and 30% RH at an IR-corrected voltage of 0.84 V, and at 60° C. and 80% RH at an IR-corrected voltage of 0.84 V. [Diagram 5] 1 shows the electrochemically effective surface area of ​​platinum in the electrode catalysts obtained in Examples 1 and 2 and Comparative Examples 1 and 2.

[0016] [Figure 6] 1 shows the proton transfer resistance of the catalyst layer of the electrode catalysts obtained in Examples 1 and 2 and Comparative Examples 1 and 2 at a temperature of 82° C. and a humidity of 30% RH. [Figure 7] 1 shows the performance ratios of the cells obtained in Example 1 and Comparative Examples 3 and 4. [Figure 8]Mass activity at a temperature of 82° C., a humidity of 30% RH and an IR-corrected voltage of 0.84 V relative to the mode diameter of the air electrode catalyst support. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] [Configuration 1] A porous carrier having a pore size of more than 6 nm and not more than 20 nm; Catalyst particles supported in the pores of the porous support; Carbon filled in the pores; Equipped with The relative carbon loading W, expressed by the following formula (1), is greater than 0 g / mL and less than 0.23 g / mL. Electrocatalyst. W = R1 / {V × (100 / R2)} … (1) however, R1 is the carbon loading per mass of the porous support [g / g]; V is the pore volume [mL / g] of the catalyst precursor A in which the catalyst particles are supported in the pores of the porous support, R2 is the mass ratio [%] of the porous support contained in the catalyst precursor A.

[0018] [Configuration 2] 2. The electrode catalyst according to claim 1, wherein the pore volume of the porous support is 0.05 mL / g or more and 2.0 mL / g or less.

[0019] [Configuration 3] 3. The electrode catalyst according to claim 1 or 2, wherein the average particle diameter of the porous support is 20 nm or more and 500 nm or less.

[0020] [Configuration 4] A first step of preparing a catalyst precursor A in which catalyst particles are supported in pores of a porous support having a pore diameter of more than 6 nm and not more than 20 nm; a second step of preparing a liquid carbon precursor containing a carbon source, dropping the liquid carbon precursor into the catalyst precursor A in an amount 1.5 times or less of the pore volume of the catalyst precursor A to obtain a catalyst precursor B in which the liquid carbon precursor is filled in the pores; a third step of heat-treating the catalyst precursor B to obtain a catalyst precursor C in which the carbon source is fixed in the pores; a fourth step of heat-treating the catalyst precursor C in a non-oxidizing atmosphere at a temperature of 500° C. or more and 1000° C. or less to carbonize the carbon source; The present invention relates to a method for producing an electrode catalyst.

[0021] An embodiment of the present invention will be described in detail below. [1. Electrocatalyst] The electrode catalyst according to the present invention is A porous carrier having a pore size of more than 6 nm and not more than 20 nm; Catalyst particles supported in the pores of the porous support; Carbon filled in the pores; It is equipped with:

[0022] [1.1. Porous carrier] [1.1.1. Materials] The material of the porous carrier is not particularly limited as long as it is a conductive material. Examples of the material of the porous carrier include: (a) Porous carbon such as mesoporous carbon, (b) SnO2, nonstoichiometric titanium dioxide (TiO x ) or other porous conductive oxides made of conductive metal oxides or composite metal oxides. etc.

[0023] [1.1.2. Pore diameter] "Pore diameter" refers to the mode diameter, i.e., the pore diameter at which the pore volume is maximum (the most frequent peak value), obtained by analyzing the data on the adsorption side of the nitrogen adsorption isotherm of the porous support using the BJH method.

[0024] Porous supports with pore sizes exceeding 6 nm are generally prone to performance degradation in low humidity environments. This is because: (a) The ionomer penetrates into the pores, and the catalyst particles supported in the pores are poisoned by the ionomer, and (b) There is a shortage of ionomer outside the pores, which weakens the connection of the proton conductive paths in the electrode thickness direction. It is thought that. In contrast, when the present invention is applied to a porous support having a pore size of more than 6 nm, the performance degradation in a low humidity environment is suppressed. This is believed to be because the ionomer is less likely to penetrate into the pores of the porous support by filling the pores with an appropriate amount of carbon. The pore size may be 8 nm or more, or 10 nm or more.

[0025] However, if the pore diameter is too large, the carbon source is likely to decompose or vaporize during heat treatment, the carbonization rate decreases, and it may not be possible to fill the amount of carbon necessary to suppress the penetration of the ionomer. Therefore, the pore diameter must be 20 nm or less. The pore diameter is preferably 18 nm or less, 16 nm or less, or 14 nm or less.

[0026] 1.1.3. Pore volume The "pore volume" of a porous carrier refers to the volume of the pores calculated from the amount of nitrogen absorbed when P / P0 = 0 to 0.95 in a nitrogen adsorption isotherm measured for the porous carrier.

[0027] If the pore volume of the porous support is too small, it becomes difficult to support catalyst particles in the pores. Therefore, the pore volume is preferably 0.05 mL / g or more. The pore volume is more preferably 0.10 mL / g or more, or 0.50 mL / g or more. On the other hand, if the pore volume is too large, the ratio of the volume of the pore walls to the volume of the porous carrier becomes small. As a result, the strength of the pore structure decreases, which may cause problems in terms of durability. Therefore, the pore volume is preferably 2.0 mL / g or less. The pore volume is more preferably 1.8 mL / g or less, or 1.6 mL / g or less.

[0028] [1.1.4. Average particle size] The "particle size" of the porous carrier refers to the length in the minor axis direction of each primary particle constituting the porous carrier, as measured under SEM observation. The "average particle size" of a porous carrier refers to the average particle size of 50 or more randomly selected primary particles.

[0029] If the average particle size of the porous support is too small, the gaps between the porous support become small, and the resistance to the movement of the reaction gas (hydrogen or oxygen) may increase. In addition, the drainage of water generated by the reaction may decrease, and the cell performance may decrease. Therefore, the average particle size is preferably 20 nm or more. The average particle size is more preferably 50 nm or more, or 75 nm or more.

[0030] On the other hand, if the average particle size of the porous carrier is too large, the movement distance of protons and reaction gases (hydrogen and oxygen) inside the porous carrier becomes long, and the movement resistance may become large. In addition, the drainage of water generated by the reaction may decrease, and the cell performance may decrease. Therefore, the average particle size is preferably 500 nm or less. The average particle size is more preferably 400 nm or less, 300 nm or less, or 200 nm or less.

[0031] Structure The porous support may be in the form of isolated particles or may have a structure in which porous primary particles are interconnected. It is particularly preferable for the porous support to have a structure in which porous primary particles are linked together like beads (hereinafter, this is also referred to as a "beaded structure"). When an electrode catalyst is produced using a porous support having a beaded structure and a catalyst layer is formed using this, a large amount of voids can be introduced into the catalyst layer. As a result, the movement resistance of the reaction gas is reduced, or water drainage is improved.

[0032] [1.2. Catalyst particles] [1.2.1. Place of support] The catalyst particles are supported at least in the pores of the porous support. The catalyst particles may be supported on the outer surface of the porous support in addition to in the pores of the porous support. In order to suppress poisoning of the catalyst particles by the ionomer, the greater the proportion of the catalyst particles supported in the pores of the porous support, the better.

[0033] [1.2.2. Materials] In the present invention, the material of the catalyst particles is not particularly limited as long as it is a material that exhibits oxygen reduction reaction activity or hydrogen oxidation reaction activity. Examples of the material of the catalyst particles include: (a) Precious metals (Pt, Au, Ag, Pd, Rh, Ir, Ru, Os), (b) An alloy containing two or more precious metal elements; (c) Alloys containing one or more precious metal elements and one or more base metal elements (e.g., Fe, Co, Ni, Cr, V, Ti, etc.); (d) metal oxynitride; (e) Carbon alloy etc.

[0034] [1.2.3. Average particle size] The "average particle size" of a catalyst particle refers to the average maximum dimension of the catalyst particle measured under a microscope for at least 20 randomly selected catalyst particles.

[0035] The average particle size of the catalyst particles is not particularly limited, and the most suitable average particle size can be selected according to the purpose. In general, if the average particle size of the catalyst particles is too small, the catalyst particles tend to dissolve. Therefore, the average particle size is preferably 1 nm or more. On the other hand, if the average particle size of the catalyst particles is too large, the mass activity decreases. Therefore, the average particle size of the catalyst particles is preferably 20 nm or less. The average particle size is more preferably 10 nm or less, or 5 nm or less.

[0036] 1.2.4. Loading amount The "loading amount" of the catalyst particles refers to the ratio of the mass of the catalyst particles to the total mass of the porous support and the catalyst particles.

[0037] In the present invention, the amount of catalyst particles supported is not particularly limited, and an optimal amount can be selected depending on the purpose. In general, if the amount of catalyst particles supported is too small, the thickness of the catalyst layer required to obtain a predetermined basis weight becomes large, and the electronic resistance, proton resistance, and / or gas diffusion resistance of the catalyst layer may increase. Therefore, the amount of catalyst particles supported is preferably 5 mass% or more. The amount is more preferably 10 mass% or more, or 15 mass% or more.

[0038] On the other hand, if the amount of catalyst particles supported is excessive, the catalyst particles may aggregate on the surface of the support, which may result in a decrease in the activity of the electrode catalyst. Therefore, the amount of catalyst particles supported is preferably 60 mass% or less. The amount is more preferably 50 mass% or less, or 40 mass% or less.

[0039] [1.3. Carbon filled in the pores] Function In the electrode catalyst according to the present invention, the pores are filled with carbon, which is different from the conventional electrode catalyst. The carbon filled in the pores is intended to adequately cover the surfaces of the catalyst particles supported in the pores and prevent the acid groups of the ionomer from being adsorbed on the catalyst particle surfaces. Such a fuel cell catalyst containing carbon is obtained by filling the pores of the porous support supporting the catalyst particles with a carbon source and carbonizing the carbon source. Details of the carbon filling method will be described later.

[0040] 1.3.2. Relative carbon loading "Relative carbon loading" refers to the carbon loading per mass of the porous support relative to the volume of pores per mass of the porous support (ie, the pore volume of the porous support). More specifically, the "relative carbon loading" refers to a value expressed by the following formula (1). W = R1 / {V × (100 / R2)} … (1) however, R1 is the carbon loading per mass of the porous support [g / g]; V is the pore volume [mL / g] of the catalyst precursor A in which the catalyst particles are supported in the pores of the porous support, R2 is the mass ratio [%] of the porous support contained in the catalyst precursor A.

[0041] The term "carbon loading amount" refers to the total mass of carbon newly introduced into the porous support (catalyst precursor A) supporting catalyst particles. The term "carbon loading amount per mass of the porous support" refers to the value obtained by dividing the carbon loading amount by the total mass of the porous support contained in the catalyst precursor A. When carbon is introduced into the porous support by the method described below, if an excess amount of carbon source is used, some of the generated carbon may be present on the outer surface of the porous support. In the present invention, the term "carbon loading amount" includes not only the carbon loaded in the pores of the porous support, but also the carbon attached to the outer surface of the porous support.

[0042] Generally, the higher the relative carbon loading, the less likely the catalyst particles supported in the pores will be poisoned by the ionomer, and the higher the mass activity. To achieve this effect, the relative carbon loading must be greater than 0 g / mL. The relative carbon loading is preferably 0.01 g / mL or more, 0.02 g / mL or more, or 0.03 g / mL or more.

[0043] On the other hand, if the relative carbon loading is excessive, the carbon coating on the surface of the catalyst particles becomes thick, which may result in a decrease in mass activity. Therefore, the relative carbon loading must be less than 0.23 g / mL. The relative carbon loading is preferably 0.21 g / mL or less, 0.175 g / mL or less, 0.150 g / mL or less, 0.125 g / mL or less, or 0.120 g / mL or less.

[0044] [2. Manufacturing method of electrode catalyst] The method for producing an electrode catalyst according to the present invention includes the steps of: A first step of preparing a catalyst precursor A in which catalyst particles are supported in pores of a porous support having a pore diameter of more than 6 nm and not more than 20 nm; a second step of preparing a liquid carbon precursor containing a carbon source, dropping the liquid carbon precursor into the catalyst precursor A in an amount 1.5 times or less of the pore volume of the catalyst precursor A to obtain a catalyst precursor B in which the liquid carbon precursor is filled in the pores; a third step of heat-treating the catalyst precursor B to obtain a catalyst precursor C in which the carbon source is fixed in the pores; a fourth step of heat-treating the catalyst precursor C in a non-oxidizing atmosphere at a temperature of 500° C. or more and 1000° C. or less to carbonize the carbon source; It is equipped with:

[0045] [2.1. 1st step] First, a catalyst precursor A is prepared in which catalyst particles are supported in the pores of a porous support having a pore diameter of more than 6 nm and not more than 20 nm (first step).

[0046] [2.1.1. Porous carrier] The porous carrier may be a commercially available material as is, or may be one produced by various methods.

[0047] For example, mesoporous carbon is (a) preparing mesoporous silica; (b) Precipitating carbon into the pores of mesoporous silica to produce a silica / carbon composite; (c) Removing silica from silica / carbon composites (See, for example, References 1 and 2). [Reference 1] JP 2022-154694 A [Reference 2] JP 2021-084852 A

[0048] In addition, the porous conductive oxide is (a) preparing mesoporous carbon; (b) Precipitating a conductive oxide in the pores of the mesoporous carbon to produce a carbon / conductive oxide composite; (c) Removing carbon from the carbon / conductive oxide composite (See, for example, Reference 3). [Reference 3] JP 2022-077821 A

[0049] Mesoporous silica can be produced by polycondensing a silica source in a reaction solution containing a silica source, a surfactant, and a catalyst. In this case, the thickness of the pore walls and the pore size of the mesoporous silica can be controlled by controlling the types and concentrations of the raw materials contained in the reaction solution.

[0050] When mesoporous carbon is produced using mesoporous silica as a template, the thickness of the pore walls of the mesoporous silica is closely correlated with the pore size of the mesoporous carbon. Furthermore, when mesoporous silica is used as a first mold to produce mesoporous carbon, and the resulting mesoporous carbon is then used as a second mold to produce a porous conductive oxide, the pore size of the mesoporous silica is strongly correlated with the pore size of the porous conductive oxide. Therefore, when mesoporous silica is used as a template to produce mesoporous carbon or porous conductive oxide, optimizing the conditions for producing the mesoporous silica makes it possible to obtain a porous support having a pore size of more than 6 nm and not more than 20 nm.

[0051] [2.1.2. Support of catalyst particles] The method for supporting the catalyst particles on the porous carrier is not particularly limited, and an optimal method can be selected depending on the purpose. For example, when a porous support and a Pt precursor are dispersed in a solvent and a reducing agent is added to the dispersion, Pt fine particles can be supported on the surface of the porous support.

[0052] [2.2. 2nd process] Next, a liquid carbon precursor containing a carbon source is prepared, and the liquid carbon precursor is dropped into the catalyst precursor A in an amount 1.5 times or less the pore volume of the catalyst precursor A (second step). This results in a catalyst precursor B in which the pores are filled with the liquid carbon precursor.

[0053] [2.2.1. Liquid carbon precursor] "Liquid carbon precursor" means (a) a liquid carbon source; (b) A solution of a liquid carbon source diluted in a solvent, or (c) A solution of a solid carbon source dissolved in a solvent This refers to.

[0054] The term "carbon source" refers to a substance capable of producing carbon by pyrolysis. Specific examples of such carbon sources include: (1) A polymer precursor that is liquid at room temperature and is thermally polymerizable (e.g., furfuryl alcohol, aniline, etc.), (2) A mixture of aqueous carbohydrate solutions and acids (e.g., mixtures of monosaccharides such as sucrose, xylose, glucose, etc., or disaccharides or polysaccharides with acids such as sulfuric acid, hydrochloric acid, nitric acid, or phosphoric acid), (3) A mixture of two-component curing polymer precursors (e.g., phenol and formalin, etc.), etc.

[0055] The solvent may be any solvent that can dilute or dissolve the carbon source and can introduce the liquid carbon precursor into the pores of the porous support. For example, when the surface of the porous support is hydrophilic, it is preferable to use a hydrophilic solvent as the solvent for diluting or dissolving the carbon source. On the other hand, when the surface of the porous support is hydrophobic, it is preferable to use a hydrophobic solvent as the solvent for diluting or dissolving the carbon source.

[0056] When the carbon source is diluted or dissolved in a solvent, the concentration of the carbon source in the solution is not particularly limited, and an optimal concentration can be selected according to the purpose. In general, the lower the concentration of the carbon source in the solution, the smaller the amount of carbon introduced into the pores in one filling. Therefore, when a substance that produces a relatively large amount of carbon by pyrolysis is used as the carbon source, it is preferable to dilute the carbon source with an appropriate amount of solvent.

[0057] [2.2.2. Dripping amount] "Catalyst precursor A" refers to a porous support having a pore diameter of more than 6 nm and not more than 20 nm in which catalyst particles are supported within the pores (that is, an electrode catalyst before carbon is filled). The "pore volume" of catalyst precursor A refers to the volume of the pores calculated from the amount of nitrogen absorbed when P / P0 = 0 to 0.95 in the nitrogen adsorption isotherm measured for catalyst precursor A.

[0058] When the liquid carbon precursor is dropped into catalyst precursor A, catalyst precursor B is obtained in which the liquid carbon precursor is filled in the pores. In this case, if the amount of liquid carbon precursor dropped is too small, the amount of liquid carbon precursor filled in the pores (i.e., the amount of carbon filled in the pores) may be excessively small. Therefore, the amount of liquid carbon precursor dropped is preferably 0.1 times or more the pore volume of catalyst precursor A. The amount dropped is more preferably 0.3 times or more, or 0.5 times or more the pore volume of catalyst precursor A.

[0059] On the other hand, if the amount of liquid carbon precursor dripped is excessive, the pores may be filled with excess carbon, which may reduce the mass activity of the electrode catalyst. In addition, the excess carbon may be precipitated outside the pores. Therefore, the amount of liquid carbon precursor dripped is preferably 1.5 times or less the pore volume of catalyst precursor A. More preferably, the amount of dripped is 1.3 times or less, 1.1 times or less, or 1.0 times or less the pore volume of catalyst precursor A.

[0060] [2.3. Third step] Next, the catalyst precursor B is heat-treated (third step), thereby obtaining a catalyst precursor C in which the carbon source is fixed in the pores.

[0061] The heat treatment is carried out to polymerize the carbon source and convert it into a non-volatile compound. The heat treatment conditions are not particularly limited as long as the conditions are such that the carbon source can be polymerized. The optimal heat treatment conditions vary depending on the type of carbon source. For example, when furfuryl alcohol is used as the carbon source, catalyst precursor B is preferably heated at 110° C. to 130° C. for 5 to 15 hours. When a mixture of sucrose and sulfuric acid is used as the carbon source, it is preferable to heat the mixture at 90° C. to 110° C. for 1 to 3 hours, and then at 150° C. to 170° C. for 5 to 7 hours.

[0062] [2.4. 4th step] Next, the catalyst precursor C is heat-treated in a non-oxidizing atmosphere at a temperature of 500° C. to 1000° C. to carbonize the carbon source (fourth step), thereby obtaining a fuel cell catalyst according to the present invention.

[0063] The heat treatment must be carried out in a non-oxidizing atmosphere to prevent oxidation of carbon. (a) In an inert gas atmosphere such as N2 or Ar, or (b) In vacuum This refers to.

[0064] If the heating temperature is too low, the carbonization of the carbon source will be insufficient. Therefore, the heating temperature must be 500° C. or higher. The heating temperature is preferably 550° C. or higher, or 600° C. or higher. On the other hand, if the heating temperature is too high, the catalyst particles may aggregate or become coarse, resulting in a decrease in the catalytic reaction area. Therefore, the heating temperature must be 1000° C. or less. The heating temperature is preferably 900° C. or less, or 800° C. or less.

[0065] In addition, when a sufficient amount of carbon cannot be filled into the pores by one cycle of filling, fixing, and carbonization of the carbon source, the steps of filling (second step), fixing (third step), and carbonization (fourth step) may be repeated multiple times.

[0066] [3. Effect] When a catalyst layer is made using an electrode catalyst in which catalyst particles are supported on a porous support with a pore size of more than 6 nm, the performance tends to decrease in a low humidity environment. This is thought to be because the ionomer penetrates into the pores and poisons the catalyst particles inside the pores. In contrast, when catalyst particles are loaded into the pores of a porous support with a pore size of more than 6 nm and then the pores are filled with carbon, the performance degradation in a low humidity environment is suppressed. This is thought to be because the carbon filled in the pores suppresses the penetration of the ionomer into the pores.

[0067] Generally, the lower the humidity, the more easily the acid groups of the ionomer are adsorbed onto the surface of the catalyst particles, and therefore the lower the humidity, the greater the effect of suppressing the adsorption of acid groups onto the catalyst particles by filling with carbon. Furthermore, in the case where the pores of the porous support carrying the catalyst particles are filled with carbon, optimizing the relative carbon filling amount also suppresses the performance degradation under highly humidified conditions. Therefore, the electrode catalyst according to the present invention exhibits high performance under a wide range of humidity environments from low to high humidity environments or in a wide range of current densities. EXAMPLES

[0068] (Examples 1 to 2, Comparative Examples 1 to 8) [1. Sample preparation] [1.1. Preparation of electrode catalyst] 1.1.1. Example 1 For catalyst precursor A, platinum-supported carbon (Pt loading amount: 40 mass%) in which Pt was supported on porous carbon having a pore diameter of 7.7 nm was used. The liquid carbon precursor used was a sucrose solution (sucrose content: 30 mass%) prepared by dissolving sucrose in a 0.25 M aqueous sulfuric acid solution.

[0069] The liquid carbon precursor was added dropwise to the catalyst precursor A to fill the pores with the liquid carbon precursor, thereby obtaining a catalyst precursor B. The amount of the liquid carbon precursor added was set to be the same as the pore volume of the catalyst precursor A, which had been determined in advance. Next, catalyst precursor B was subjected to a heat treatment for fixing the carbon source to obtain catalyst precursor C. The heat treatment for fixing the carbon source was performed by heating catalyst precursor B in air at 100°C for 2 hours, and then further increasing the temperature to 160°C and heating for 6 hours. Next, catalyst precursor C was subjected to a heat treatment for carbonizing the carbon source to obtain an electrode catalyst. The heat treatment for carbonization was performed by heating catalyst precursor C at 550°C for 6 hours under a nitrogen flow (1 L / min), and then further increasing the temperature to 700°C and heating for 6 hours.

[0070] 1.1.2. Example 2 For catalyst precursor A, the same platinum-supported carbon as in Example 1 was used. The liquid carbon precursor was a furfuryl alcohol (FA) solution (FA content: 30 vol%) prepared by diluting FA with water.

[0071] The liquid carbon precursor was added dropwise to the catalyst precursor A to fill the pores with the liquid carbon precursor, thereby obtaining a catalyst precursor B. The amount of the liquid carbon precursor added was set to be the same as the pore volume of the catalyst precursor A, which had been determined in advance. Next, catalyst precursor B was subjected to a heat treatment for fixing the carbon source to obtain catalyst precursor C. The heat treatment for fixing the carbon source was performed by heating catalyst precursor B in air at 120° C. for 10 hours. Next, the catalyst precursor C was subjected to a heat treatment for carbonizing the carbon source to obtain an electrode catalyst. The heat treatment conditions for carbonization were the same as those in Example 1.

[0072] [1.1.3. Comparative Example 1] The unloaded platinum-supported carbon used in Example 1 was directly subjected to the test.

[0073] [1.1.4. Comparative Example 2] The carbon source was filled, fixed, and carbonized in the same manner as in Example 2, except that a FA solution (FA amount: 50 vol%) prepared by diluting FA with water was used as the liquid carbon precursor, to obtain an electrode catalyst.

[0074] [1.1.5. Comparative Example 3] In the same manner as in Example 3 of Patent Document 3, an electrode catalyst was prepared in which Pt was supported on the surface of a solid carbon support, and the surface of the Pt was further covered with a dopamine-derived carbon film.

[0075] [1.1.6. Comparative Example 4] In the same manner as in Example 1 of Patent Document 2, an electrode catalyst was prepared in which Pt was supported on the surface of a solid carbon support, and the surface of the Pt was further coated with a nitrogen-containing carbon film derived from dopamine and polymelamine.

[0076] [1.1.7. Comparative Examples 5 to 8] Monodispersed spherical carbon porous bodies having a pore size of 3.8 nm were prepared in the same manner as in Example 1 of Patent Document 1. Pt was supported on these bodies to obtain an electrode catalyst (Comparative Example 5). Monodispersed spherical carbon porous bodies having a pore size of 4.8 nm were prepared in the same manner as in Example 2 of Patent Document 1. Pt was supported on these bodies to obtain an electrode catalyst (Comparative Example 6). Monodispersed spherical carbon porous bodies having a pore size of 7.8 nm were prepared in the same manner as in Comparative Example 1 of Patent Document 1. Pt was supported on these bodies to obtain an electrode catalyst (Comparative Example 7). Monodispersed spherical carbon porous bodies having a pore size of 9.9 nm were prepared in the same manner as in Comparative Example 2 of Patent Document 1. Pt was supported on these bodies to obtain an electrode catalyst (Comparative Example 8).

[0077] [1.2. Fabrication of membrane electrode assembly (MEA)] An air electrode catalyst layer was prepared using either a carbon-filled or uncarbon-filled electrode catalyst. Nafion (registered trademark) solution (D2020) was used as the ionomer. The ratio (I / C) of the amount of ionomer (I) to the amount of carbon (C) contained in the electrode catalyst was set to 1.3. In addition, an anode catalyst layer was produced using commercially available platinum-supported carbon and Nafion (registered trademark) solution (D2020). An air electrode catalyst layer and an anode catalyst layer were bonded to both sides of an electrolyte membrane (Nafion (registered trademark) membrane, NR211) by hot pressing to obtain an MEA. Table 1 shows the Pt coverage and the type of liquid carbon precursor of the air electrode catalyst layers obtained in Examples 1 and 2 and Comparative Examples 1 and 2.

[0078] [Table 1]

[0079] 2. Test Method 2.1. Carbon loading measurement To determine the carbon loading amount of the electrode catalyst, TG measurement was performed under air flow (100 mL / min) at a temperature increase rate of 10°C / min from room temperature to 900°C. Furthermore, the carbon loading amount (W1) was calculated using the following formulas (1) to (6). The obtained carbon loading amount (W1) was divided by the mass of the porous carbon to calculate the "carbon loading amount per mass of porous support," and this was further divided by the pore volume of the porous carbon to calculate the relative carbon loading amount (g / mL).

[0080] Carbon loading (W1) = W2 - W3 - W4 - W5 ... (1) Sample mass (W2) = total mass of the carbon-filled electrode catalyst … (2) Moisture content (W3) = TG reduction @200℃…(3) Pt mass (W4)=W2-TG reduction @900℃…(4) Mass of carbon support (W5) = W4 × (100-R) / R … (5) R = Pt loading rate (%) of the electrode catalyst without carbon filling … (6)

[0081] [2.2. Evaluation of electrode characteristics and cell performance] MEA electrode area: 1 cm 2 The cell was then set in the evaluation bench and assembled. Furthermore, the electrode characteristics and cell performance were evaluated according to the following procedures. (1) Break-in at temperature: 60°C, humidity: 80% RH, and mass activity evaluation (2) Mass activity evaluation at temperature: 82°C and humidity: 30% RH (3) Evaluation of the electrochemical effective surface area of ​​Pt and the proton transfer resistance of the catalyst layer at a temperature of 60°C and a humidity of 80% RH (4) Evaluation of the electrochemical effective surface area of ​​Pt and the proton transfer resistance of the catalyst layer at a temperature of 82°C and a humidity of 30% RH Details of each evaluation are provided below.

[0082] [2.2.1. Mass activity evaluation] The IV characteristics were evaluated, and the mass activity was calculated by dividing the current value at 0.84 V (IR corrected voltage) by the Pt coverage. The measurement conditions were as follows: Air electrode: Air, 2L / min, atmospheric pressure +50kPa Fuel electrode: H2, 0.5L / min, atmospheric pressure +30kPa Voltage sweep: 10mV / s, 0~1.0V

[0083] [2.2.2. Evaluation of electrochemically active surface area (ECSA) of Pt] Cyclic voltammogram (CV) measurements were performed to calculate the hydrogen desorption charge per unit platinum area (210 μC / cm 2 The ECSA of Pt was calculated by dividing the ECSA by the following: Air electrode: N2, 1L / min, atmospheric pressure, Fuel electrode: 10%H2 / N2, 1L / min, atmospheric pressure Voltage sweep: 50mV / s, 115~1000mV vs RHE

[0084] [2.2.3. Evaluation of catalyst layer proton transfer resistance] The impedance versus frequency was measured by an AC impedance method, and the proton transfer resistance in the catalyst layer was calculated from the Nyquist plot. The measurement conditions were as follows: Air electrode: N2, 1000mL / min, atmospheric pressure Anode: 10%H2 / N2, 1000mL / min, atmospheric pressure Potential: 400mV vs RHE Frequency: 15kHz~1Hz Amplitude: 5mV

[0085] [3. Results] 3.1. Relative carbon loading 1 shows the relative carbon loading amounts of the electrode catalysts obtained in Examples 1 and 2, and Comparative Example 2. From FIG. 1, it can be seen that the ranking of the relative carbon loading amounts is Example 1<Example 2<Comparative Example 2.

[0086] [3.2. Evaluation of electrode characteristics and cell performance] [3.2.1. Mass activity evaluation] Figure 2 shows the mass activity of the electrode catalysts obtained in Examples 1 and 2 and Comparative Examples 1 and 2 at a temperature of 82°C and a humidity of 30% RH at an IR corrected voltage of 0.84 V. Figure 3 shows the mass activity of the electrode catalysts obtained in Examples 1-2 and Comparative Examples 1-2 at a temperature of 60°C and a humidity of 80% RH at an IR corrected voltage of 0.84 V. Furthermore, Figure 4 shows the relationship between the relative carbon loading amount and the mass activity at a temperature of 82°C and a humidity of 30% RH at an IR corrected voltage of 0.84 V, and the mass activity at a temperature of 60°C and a humidity of 80% RH at an IR corrected voltage of 0.84 V.

[0087] 2 shows that the mass activities under low humidification conditions of Examples 1 and 2 are higher than that of the carbon-unfilled Comparative Example 1. Also, FIG 3 shows that the mass activities under high humidification conditions of Examples 1 and 2 are equivalent to or slightly lower than that of the carbon-unfilled Comparative Example 1, and no significant decrease in mass activity due to carbon filling is observed. On the other hand, in Comparative Example 2, which had a large carbon loading, no improvement in mass activity under low humidity conditions due to carbon loading was observed, and in Comparative Example 2, mass activity under high humidity conditions was significantly reduced.

[0088] From FIG. 4, it can be seen that in order to make the mass activity under low humidification conditions equal to or greater than that of Comparative Example 1, the relative carbon loading amount should be set to 0.21 g / mL or less. The mass activity of Comparative Example 1 under high humidity conditions is defined as MA1, the mass activity of the evaluation target under high humidity conditions is defined as MA2, and the activity decrease rate (%) under high humidity conditions is defined as (MA1-MA2) x 100 / MA1. It can be seen from Fig. 4 that in order to keep the activity decrease rate under high humidity conditions at 20% or less, the relative carbon loading amount should be set to 0.12 g / mL or less.

[0089] [3.2.2. Evaluation of electrochemically active surface area (ECSA) of Pt] Figure 5 shows the electrochemically effective surface area of ​​platinum in the electrode catalysts obtained in Examples 1 and 2 and Comparative Examples 1 and 2. It can be seen from Figure 5 that the ECSA of Examples 1 and 2 is equivalent to that of Comparative Example 1. This indicates that protons are conducted to Pt in the pores even when carbon is filled in the pores. On the other hand, the ECSA of Comparative Example 2 was smaller than that of Comparative Example 1. This indicates that when the carbon loading amount becomes excessive, protons are less likely to be conducted to Pt in the pores. Therefore, it is considered that Comparative Example 2 had lower mass activity under low and high humidification conditions than Comparative Example 1.

[0090] [3.2.3. Evaluation of catalyst layer proton transfer resistance] Fig. 6 shows the proton transfer resistance of the catalyst layer at a temperature of 82°C and a humidity of 30% RH for the electrode catalysts obtained in Examples 1 and 2 and Comparative Examples 1 and 2. Fig. 6 shows that the proton transfer resistance of the catalyst layer in Examples 1 and 2 and Comparative Example 2 is lower than that in Comparative Example 1. It is also shown that the greater the carbon loading amount, the lower the proton transfer resistance of the catalyst layer. The reason why the proton resistance of the catalyst layer decreases with an increase in the carbon loading amount is believed to be that the greater the carbon loading amount, the more the penetration of the ionomer into the pores is suppressed, and the amount of ionomer increases on the outer periphery of the porous support.

[0091] [3.2.4. Relative performance] 7 shows the performance ratios of the cells obtained in Example 1 and Comparative Examples 3 and 4. Here, the "performance ratio" refers to the ratio of the cell performance of Comparative Examples 3 and 4 to the cell performance of Example 1. In addition, "cell performance" is (a) Mass activity (MA-30%RH) or current density (CD-30%RH) at IR-corrected voltage of 0.84 V at temperature of 82° C. and humidity of 30% RH, or (b) Mass activity (MA-80%RH) or current density (CD-80%RH) at IR-corrected voltage of 0.84 V at temperature: 60°C and humidity: 80%RH This refers to.

[0092] 7, it can be seen that the MA at 30% RH in Comparative Examples 3 and 4 are all higher than that in Example 1, but the other cell performances are all lower than that in Example 1. It can be said from Fig. 7 that the electrode catalyst according to the present invention exhibits higher performance in a wider humidity range from low humidity to high humidity and in a wider current density range than Comparative Examples 3 and 4.

[0093] 3.2.5. Effect of pore size on mass activity Figure 8 shows the mass activity at a temperature of 82°C, humidity of 30% RH, and IR-corrected voltage of 0.84 V versus the mode diameter of the air electrode catalyst support. The horizontal axis of Figure 8 represents the pore diameter of the catalyst support (the mode diameter of the pore diameter distribution obtained by BJH analysis of the nitrogen adsorption measurement). From Figure 8, it can be seen that the MA decreases as the pore size increases when carbon is not loaded. This is thought to be because, when carbon is not loaded, the amount of ionomer that penetrates into the pores increases as the pore size increases. This is also thought to be because the proportion of Pt poisoned by the ionomer (i.e., the proportion of Pt that reduces catalytic activity) increases.

[0094] From the above results, it was found that simply supporting Pt in the pores of a support with a large pore diameter reduces the mass activity in a low humidity environment. On the other hand, it was found that by supporting Pt in the pores of a support with a large pore diameter and filling the pores with an appropriate amount of carbon, the decrease in activity due to ionomer poisoning is suppressed, making it possible to use a support with a large pore diameter.

[0095] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]

[0096] The electrode catalyst according to the present invention can be used as an electrode catalyst for an air electrode catalyst layer and / or an anode catalyst layer of a polymer electrolyte fuel cell, an electrode catalyst for various electrochemical devices, and the like.

Claims

1. A porous support having a pore size of more than 6 nm and not more than 20 nm; Catalyst particles supported in the pores of the porous support; Carbon filled in the pores; Equipped with The relative carbon loading W represented by the following formula (1) is greater than 0 g / mL and less than 0.23 g / mL. Electrocatalyst. W=R 1 / {V×(100 / R 2 )} …(1) however, R 1 is the carbon loading per mass of the porous support [g / g], V is the pore volume [mL / g] of the catalyst precursor A in which the catalyst particles are supported in the pores of the porous support, R 2 represents the mass ratio [%] of the porous support contained in the catalyst precursor A.

2. 2. The electrode catalyst according to claim 1, wherein the pore volume of the porous support is 0.05 mL / g or more and 2.0 mL / g or less.

3. 2. The electrode catalyst according to claim 1, wherein the average particle diameter of the porous support is 20 nm or more and 500 nm or less.

4. A first step of preparing a catalyst precursor A in which catalyst particles are supported in pores of a porous support having a pore diameter of more than 6 nm and not more than 20 nm; a second step of preparing a liquid carbon precursor containing a carbon source, dropping the liquid carbon precursor into the catalyst precursor A in an amount 1.5 times or less of the pore volume of the catalyst precursor A to obtain a catalyst precursor B in which the liquid carbon precursor is filled in the pores; a third step of heat-treating the catalyst precursor B to obtain a catalyst precursor C in which the carbon source is fixed in the pores; a fourth step of heat-treating the catalyst precursor C in a non-oxidizing atmosphere at a temperature of 500° C. or more and 1000° C. or less to carbonize the carbon source; The present invention relates to a method for producing an electrode catalyst.

Citation Information

Patent Citations

  • Electrode catalyst and production method thereof, and electrode for fuel cell and fuel cell

    JP2020136109A

  • Electrode catalyst, manufacturing method thereof, electrode for fuel cell, and fuel cell

    JP2022142887A

  • Monodispersed porous carbon spheres and polymer electrolyte fuel cells

    JP7116564B2